The Effects of Inflation, Bi Rate, and Government Securi-ties Yield on the Third-Party Fund Growth of Digital Banks (A Case Study of PT Bank Jago Tbk) - Ma'ana, 'Asa Rahmatillah; Munawar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Banking digitalization continues to grow in line with technological advances. Many digital banks have emerged as alternatives to conventional banks. Similar studies have been conducted, but only on conventional banks. Therefore, this study aims to analyze the effect of inflation, BI Rate, and Government Securities (SBN) yields on Bank Jago's Third Party Funds (DPK). This study uses quantitative methods with Autoregressive Distributed Lag (ARDL) and Error Correction Model (ECM) analyses to identify the short-term and long-term relationships between the independent variables and the dependent variable. The results show that in the long term, inflation has a significant effect on the growth of Bank Jago's DPK, namely on demand deposits and time deposits, and only has a significant effect on time deposits in the short term. The BI Rate has a significant effect on Bank Jago's DPK, namely demand deposits in the long term, and has a significant effect on the growth of time deposits in the short term. The yield on SBN has no significant effect on the growth of Bank Jago's DPK.